Regulating sewage pollution of Malaysian rivers and its challenges - Ariffin, Mariani; M. Sulaiman, Siti Norhafizah (Elsevier, 2015)
While sewage pollution is considered as an old problem which developed nations have already managed effectively, missing all too often in developing countries are the resources to come up with practical solution and the necessary political and legal infrastructure to support these solutions as well as the community awareness required to address the problem. Many Malaysian rivers continue to suffer from sewage pollution. This paper provided concise exposition the regulatory framework of sewage pollution control of inland surface waters under the country's existing primary federal environmental legislation. The paper then discussed regulators’ perceptions on the main causes that lead to the recurring sewage pollution problem in Malaysian rivers. Semi-structured interviews were conducted face-to-face with key informants from several relevant government bodies. They highlighted a mixture of causes to the recurring problem of sewage pollution in our rivers including insufficiency of the law and its implementation, outdated technology as well as lack of public awareness. This research gathers essential views from different authorities that can be of use by policy-makers in the efforts of improving the existing situation of sewage pollution problem in the country